The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/jp102603b
|View full text |Cite
|
Sign up to set email alerts
|

The Ultraviolet Absorption Coefficient of Melanosomes Decreases with Increasing Pheomelanin Content

Abstract: Uveal melanosomes from the iridal stroma contain both eumelanin and pheomelanin, the ratio of which varies with iris color. Herein, we report the absorption coefficient at λ ) 244 nm for individual human iridal stroma melanosomes from dark brown and blue-green irides. The melanosomes are nearly identical in size, but differ in the relative concentration composition, ranging from a eumelanin/pheomelanin ratio of 14.8:1 (dark brown) to 1.3:1 (blue-green or hazel). The absorption coefficient of the melanosome dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…It is confirmed that melanin plays the most important protective role against UV radiation in the skin …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…It is confirmed that melanin plays the most important protective role against UV radiation in the skin …”
Section: Introductionmentioning
confidence: 83%
“…In most of these experiments, the hair is treated using different chemical methods. The specific eumelanin and pheomelanin degradation products were used as markers …”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated 18 that the average path length, s, through half of the ellipsoidal melanosome is given by…”
Section: Experimental Methodsmentioning
confidence: 98%
“…57 At first glance, one might assume that this means pheomelanin has a smaller absorption cross section than eumelanin. Such a conclusion would be in stark contrast to studies on synthetic pigments, where comparable absorption coefficients are observed.…”
Section: Red and Black Simon And Pelesmentioning
confidence: 99%